Philosophical Paradigm, Prophetic Paradigm, Islamic Worldwide View on Economics: Concept and Practice for Management - Arundati, Rahajeng; Tamara, Karima; Pramusinto, Pramusinto (Institute of Research and Public Service Universitas Jenderal Soedirman, 2024)
The prophetic paradigm is a philosophical approach that explores the role of prophets and their messages in religious doctrine. This research aims to outline the various philosophical paradigms and their applications in management. In addition, the Islamic view of economics is also explained through three chronological periods, namely the Meccan period, the Medina period, and the Islamic knowledge structure period. After understanding these aspects, this research focuses on explaining the prophetic paradigm. This research is a literature research with a qualitative approach. The data was analysed using Miles and Huberman's qualitative data analysis method. The results showed that although the values drawn from this paradigm may vary among religions and traditions, there are often some common values, such as justice, compassion, and wisdom. Some of the implications of this paradigm for management practices can assist managers in implementing Islamic values in their businesses. Islamic values impact management practices through the influence of institutional and individual factors, which in turn contribute to the adoption of ethical behaviour and improved performance within the organisation.